Parenting Styles and Teachers' Teaching Styles impact on Students' Values Development - Dallasheh, Waleed (Journal of Ecohumanism, 2024)
This study examines the effect of parenting and teaching styles on students' values development within Arab society in Israel. It aimed to determine: 1) the relationship between parenting style and students’ values development from teachers’ perspectives; 2) how teaching methods using English as a Second Language (ESL) strategies affect students' values development; and 3) demographic differences (sex, role, education, types of schools) among teachers in values development and parenting styles.The sample includes 280 teachers (112 male; 168 female) from Arab high schools' students in northern Israel and 200 parents (104 male; 96 female) who participated in the questionnaire. Findings indicate that authoritative parenting, which balances warmth and control, is most effective in fostering positive values, while authoritarian and permissive styles may lead to poorer outcomes in self-esteem, motivation, and behavior. Discussion-oriented and student-centered teaching approaches promote critical thinking, empathy, and ethical reasoning. No significant differences were found in the impact of teaching and parenting styles on values development based on gender, age, or educational level of teachers, except for differences in direct and delegating teaching styles.The study concludes that parenting and teaching styles are interdependent. Supportive parenting enhances the effectiveness of constructive teaching methods, and teachers' approaches can reinforce values instilled by parents. Recommendations for Arab society include promoting authoritative parenting through educational programs, encouraging discussion-based and student-centered teaching methods via teacher training and curriculum reforms, fostering school and community collaboration, addressing cultural sensitivities, and providing teachers with necessary resources and professional development opportunities.